2014
DOI: 10.1080/09640568.2013.862166
|View full text |Cite
|
Sign up to set email alerts
|

Leadership in sustainability planning: propagating visions through empathic communication

Abstract: Despite their lack of decision-making power, planners frequently prevail in advancing strong sustainability agendas. A review of leadership and planning literature suggests that they employ collaborative practice. Using an ethnographic methodology that draws from the stories and actions of six planners with sustainability mandates, supplemented with a survey of their staff and colleagues, this research examines how they do it. Findings suggest that despite variety in their organisational contexts, the planners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…According to relevant research, shared vision represents the organizational vision of organization members and the collective concept of the organization's mission and core values [59,60]. When organizational planners have strong visions, the achievement of sustainability requirements is promoted [61]. Consequently, shaping and clarifying the shared vision of an organization and creating personal value for organization members are key to generating organizational identity.…”
Section: Influence Of Gsv On Organization Members According To Expectmentioning
confidence: 99%
“…According to relevant research, shared vision represents the organizational vision of organization members and the collective concept of the organization's mission and core values [59,60]. When organizational planners have strong visions, the achievement of sustainability requirements is promoted [61]. Consequently, shaping and clarifying the shared vision of an organization and creating personal value for organization members are key to generating organizational identity.…”
Section: Influence Of Gsv On Organization Members According To Expectmentioning
confidence: 99%
“…First, it is important that local leaders understand the importance of planning culture and collaborative actions in developing long-term vision. As Senbel (2014) argues, there are two possible ways to encourage this: local leaders are forged to understand planning concepts, or alternatively, planners should attempt to become the leaders. Second, in developing communication strategies, situational factors both from inside and outside the local environment need to be comprehended.…”
Section: Resultsmentioning
confidence: 99%
“…Leaders should be able to operate with intersectional components that exist in the place (Collinge and Gibney, 2010b). Leadership framework can help build vision, communication and relationships between actors (Senbel, 2014). Leaders can foster dialogues, persuade stakeholders to participate in the collaborative process and manage potential conflicts (Crosby and Bryson, 2005).…”
Section: Integrating Leadership and Collaborative Planningmentioning
confidence: 99%
“…Chen et al [67] indicated that enterprises should aim for environmentally friendly sustainable development and that the management of enterprises should devise a strategic development direction with explicit and common future environmental protection goals for establishing GSV. Senbel [68] stated that organization managers with a strong vision can promote the achievement of sustainability requirements. Studies have indicated that when appropriate GSV is developed, employees' environmental performance [22], organizational citizenship behavior toward the environment [69], green product development performance [70], GPPO [30], and GC [67] are enhanced.…”
Section: Influences Of Gsv On Organization Membersmentioning
confidence: 99%